Incidence and impact of dog attacks on guide dogs in the UK: an update - Moxon, Rachel; Whiteside, H.; England, Gary C.W. (BMJ Publishing Group, 2016)
Data on dog attacks on Guide Dogs’ stock were reviewed to investigate the characteristics of the attacks. An average of 11.2 attacks occurred each month. Nearly all of the attacks occurred in public areas, 68.4 per cent of victim dogs were qualified guide dogs and 55.5 per cent of victim dogs were working in harness when they were attacked. Guide Dogs’ stock were injured in 43.2 per cent of attacks and veterinary costs for attacks were estimated at £34,514.30. Over 40 per cent of qualified guide dogs’ working ability was affected and >20 per cent of qualified guide dogs required some time off from working after a dog attack. Twenty dogs were permanently withdrawn from the Guide Dogs’ programme as a result of dog attacks, 13 of which were qualified and working with guide dog owners at the time of the withdrawal; this resulted in a financial cost of >£600,000 to the charity. More importantly perhaps, temporary and permanent withdrawals have a significant impact upon the mobility and independence of guide dog owners and in many cases significantly impacted their emotional well-being.